A Multistate Markov Model for the Progression of Congestive Heart Failure Using Kolmogorov Differential Equation - Meenaxi; Singh, Dalip (Communications in Mathematics and Applications, 2022)
The reliability of individuals and human activities are vital for the new complexity of life, work and medication improvement. Markov models are grounded strategies for assessing paces of progress between phases of chronic illnesses. This paper is mainly focused on the survival analysis of a heart patient with Congestive cardiac failure. The objective of the paper is to describe the progression process of chronic heart failure (CHF), to estimate the life expectancy of patient suffering from congestive Heart failure. Explicit expression for Availability is also derived in this paper by using Kolmogorov differential equations. Graphs have been plotted to determine the behaviour of life expectancy of patient and availability analysis.